Criminal Law Enforcement Against Dealers as Drug Abuse Perpetrators in Progressive Law - Prasetyo, Wahyu (UNISSULA Semarang, 2025)
Abstract. Law enforcement aims to create justice, certainty and benefits, in relation to drug abuse, law is one alternative solution to eradicate drug abuse, because the law contains a number of rules and provisions to ensure that the norms in the law are obeyed by the community. Drug abusers more often end up in prison than given the right to rehabilitation. The dimensions of health and recovery, both physical and psychological, through rehabilitation are less considered and tend to be sidelined. The imposition of sanctions for users should be more oriented towards the aspect of rehabilitation punishment rather than prison sentences, because this is to emphasize and clarify the sanctions between drug dealers and abusers. The approach method used is normative juridical, namely a library legal research conducted by examining library materials or secondary data only using deductive thinking methods. The writing specifications use descriptive analysis, the sources and types of data used are secondary data. The data collection method is by collecting data using secondary data collection methods. The problems are analyzed with the theory of law enforcement and the theory of legal effectiveness. For drug addicts or dealers as a substitute for imprisonment sanctions adopted from the double track system model, which is a two-track system regarding sanctions in criminal penalties, namely the type of criminal sanctions and the type of action sanctions. The guarantee of legal protection provided for drug addicts is regulated through Law No. 35 of 2009 concerning Narcotics by providing rehabilitation, both medical and social rehabilitation as stated in Article 54 of the narcotics law, namely that